Extradition between Kuwait and the UK: new dispositions, old doubts - Al-Rashidi, Khaled S. (International journal of law, crime and justice, 2021)
The Extradition Treaty between Kuwait and the UK, signed in 2016, presages a new stage of cooperation in criminal justice matters. The Treaty and the related arrangements are designed to facilitate the surrender of fugitives. However, a number of factors, not least the statutory bars to extradition in UK legislation and broader apprehensions about extradition, cast doubt on the effective implementation of the Treaty, particularly for extradition requests from Kuwait. There is contestation between the ‘law enforcement expert community’ which favours ever more ‘efficient’ extradition and proponents of a ‘popular view’, such as politicians and the media, who are suspicious that more accessible extradition threatens the interests of British citizens. In this way, the new dispositions with Kuwait must contend with older doubts about extradition which are being played out with other bilateral partners, such as the US and the European Union.